Meltwater Intrusions Reveal Mechanisms for Rapid Submarine Melt at a Tidewater Glacier. Issue 2 (23rd January 2020) - Jackson, R. H.; Nash, J. D.; Kienholz, C.; Sutherland, D. A.; Amundson, J. M.; Motyka, R. J.; Winters, D.; Skyllingstad, E.; Pettit, E. C.
Abstract: Submarine melting has been implicated as a driver of glacier retreat and sea level rise, but to date melting has been difficult to observe and quantify. As a result, melt rates have been estimated from parameterizations that are largely unconstrained by observations, particularly at the near‐vertical termini of tidewater glaciers. With standard coefficients, these melt parameterizations predict that ambient melting (the melt away from subglacial discharge outlets) is negligible compared to discharge‐driven melting for typical tidewater glaciers. Here, we present new data from LeConte Glacier, Alaska, that challenges this paradigm. Using autonomous kayaks, we observe ambient meltwater intrusions that are ubiquitous within 400 m of the terminus, and we provide the first characterization of their properties, structure, and distribution. Our results suggest that ambient melt rates are substantially higher (×100) than standard theory predicts and that ambient melting is a significant part of the total submarine melt flux. We explore modifications to the prevalent melt parameterization to provide a path forward for improved modeling of ocean‐glacier interactions. Plain Language Summary: Tidewater glaciers discharge ice into the ocean through iceberg calving and submarine melting. Submarine melting has been implicated as a driver of glacier retreat and sea level rise, but melt rates have been difficult to directly observe and quantify. As a result, melt rates are typically estimated using a theory that has not been tested with observations at any tidewater glaciers. Two types of melting are expected at tidewater glaciers: Where subglacial discharge drains from outlets in the terminus, energetic upwelling plumes rise along the ice face, and theory predicts vigorous melting. Away from discharge outlets, weaker plumes form from ambient melting, and theory predicts that these ambient melt rates are effectively negligible compared to discharge‐driven melting. Here, we present new data from LeConte Glacier, Alaska, that challenges this paradigm. Using autonomous kayaks, we observe intrusions of meltwater—the product of ambient melt plumes—that are only found within 400 m of the terminus, and we provide the first characterization of their properties, structure, and distribution. Their ubiquity suggests that ambient melt rates are substantially higher than standard theory predicts and that ambient melting is a significant—but often neglected—part of the total submarine melt flux. Key Points: Near‐terminus sampling at a tidewater glacier reveals ubiquitous meltwater intrusions that are distinct from the subglacial discharge plume Meltwater intrusions are only observed within 400 m of the terminus, as they are ultimately entrained into the subglacial discharge plume Ambient melt is 2 orders of magnitude higher than standard theory predicts, suggesting a key role for ambient melt in the net ablation